2015
DOI: 10.4314/ijbcs.v9i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic potential and anther <i>in vitro</i> culture of <i>Lagenaria siceraria</i> (Molina) Standl an edible-seed cucurbit

Abstract: Lagenaria siceraria Molina has a high productive potential of fruits but the seeds weight remain low. The aim of this study is to regenerate doubled haploids from androgenesis in order to create genotypes with good agronomic characteristics. For this purpose, flower buds of six accessions namely NI185, NI202, NI215, NI276, NI356 and NI271 were pre-treated at 4 °C for 0, 1, 2, 4, 6, 7 days. To assess the ability of these accessions to induce callus, the anthers excised from the collected floral buds were cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
2
2
0
2
Order By: Relevance
“…The maximum temperature rise is recorded with the HIRHAM5 model under the RCP8.5 scenario and the minimum with the RCA4 model under the RCP4.5 scenario. This trend of increased temperature is consistent with Kouakou et al (2014) findings who indicated the same range of increased temperature for the horizon 2031 to 2040 in the Sahel region.…”
Section: Climate Change Scenarios During the Near Future (2021-2050)supporting
confidence: 81%
See 1 more Smart Citation
“…The maximum temperature rise is recorded with the HIRHAM5 model under the RCP8.5 scenario and the minimum with the RCA4 model under the RCP4.5 scenario. This trend of increased temperature is consistent with Kouakou et al (2014) findings who indicated the same range of increased temperature for the horizon 2031 to 2040 in the Sahel region.…”
Section: Climate Change Scenarios During the Near Future (2021-2050)supporting
confidence: 81%
“…Figure 5 shows the mean summer temperature change during the far future (2071 to 2100) for the RCMs and their ensemble mean. In this period, a significant warming is predicted which is in line with some works (Kouakou et al, 2014;Sylla et al, 2016) who indicated that temperature will continue to rise over all West Africa and especially in the Sahel region whatever the considered scenarios types. This possible increase of the surface temperature is associated with an increase of water demand on many sector particularly the agriculture.…”
Section: Climate Change Scenarios During the Near Future (2021-2050)supporting
confidence: 66%
“…Buds collected directly from the plant, as every type of explants introducing to the in vitro cultures, must be subjected to the disinfection process. This stage, as described by Kouakou et al (2015), is a great challenge for obtaining the aseptic cultures of all plant species. In our experiments, aseptic cultures were obtained in case of all tested methods of bud disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Las microsporas inducidas en T5 (Fig. 4 a,b,c) presentaban cambios que se observan en muchos trabajos donde se inducen embriogénesis a partir de microsporas (Soriano et al, 2013) y con pre tratamiento a temperaturas de 4º C ( Kouakou et al, 2015) como aumento de tamaño, otras empezaban un proceso de división y se encontraban cubiertas aún por una capa de exina y otras se agrupaban linealmente formando embriones tipo suspensor; al hacer una tinción fluorescente con DAPI observaron la presencia de varios núcleos en dichos proembriones. Perera et al, (2014) trabajando con anteras y microsporas de Manihot esculenta coinciden con nuestras observaciones (Fig.…”
Section: Discussionunclassified
“…Utilizó ANA, BAP, 2iP y TDZ encontrando alta producción de callos (98%) si los óvulos provenían de pimpollos florales de 22-24 mm de longitud y tratados con 3 ppm de ANA y 3 ppm de 2iP. Kouakou et al, (2015) evaluó el potencial androgénico de las anteras de Lagenaria siceraria con un pretratamiento de 0, 1, 2, 4,6 y 7 días a 4º C. Obtuvieron un 79% de callos cuando las anteras estuvieron uno y dos días a 4º C. El contar con metodologías que nos permitan obtener plantas haploides a través del cultivo de anteras, no solo en papaya sino también en otras especies, es de vital importancia, pero antes se debe comenzar a conocer las características morfológicas e histológicas que presenta un callo, lo cual es frecuente al iniciar los cultivo in vitro de anteras. Con lo expuesto el objetivo de este trabajo fue determinar el efecto del ácido naftalenacético y el 6-bencilaminopurina, a distintas concentraciones, en la inducción de callos a partir de anteras de C. papaya L. variedad criolla.…”
Section: Introductionunclassified